Indications of Optical Coherence Tomography in Keratoplasties: Literature Review - Thiago Trindade Nesi; Daniel Amorim Leite; Fábio Medina Rocha; Marco Antônio Tanure; Pedro Paulo Reis; Eduardo Büchele Rodrigues; Mauro Silveira de Queiroz Campos (Journal of Ophthalmology)
Optical coherence tomography (OCT) of the anterior segment, in particular corneal OCT, has become a reliable tool for the cornea specialist, as it provides the acquisition of digital images at high resolution with a noncontact technology. In penetrating or lamellar keratoplasties, OCT can be used to assess central corneal thickness and pachymetry maps, as well as precise measurements of deep stromal opacities, thereby guiding the surgeon to choose the best treatment option. OCT has also been used to evaluate the keratoplasty postoperative period, for early identification of possible complications, such as secondary glaucoma or donor disc detachments in endothelial keratoplasties. Intraoperatively, OCT can be used to assess stromal bed regularity and transparency in anterior lamellar surgeries, especially for those techniques in which a bare Descemet’s membrane is the goal. The purpose of this paper is to review and discuss the role of OCT as a diagnostic tool in various types of keratoplasties.